2016
DOI: 10.5603/pp.2015.0083
|View full text |Cite
|
Sign up to set email alerts
|

Nawyki żywieniowe a jakość życia pacjentów rehabilitowanych w środowiskowych domach samopomocy

Abstract: awyki żywieniowe a jakość życia pacjentów rehabilitowanych w środowiskowych domach samopomocy Eating habits to the quality of life of the patients rehabilitated ate self-help homes STRESZCZENIE Wstęp. Nawyki żywieniowe w znaczącym stopniu wpływają na zdrowie, samopoczucie oraz występowanie i intensywność objawów chorób występujących wśród pacjentów rehabilitowanych w środowiskowych domach samopomocy. Czynniki te mają znaczenie nie tylko w kwestii obiektywnej oceny zdrowia pacjentów, ale też są istotne w subiek… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…Meanwhile, this finding incomparable with Tęcza, & Pych . (2018) (27) : who studied" nursing care of a patient with systemic lupus erythematosus " and found that, more than half (55.9%) of the studied mothers were in the age group ≥ 40 years with ± SD was 39.62 ± 5.86 years and more than one third( 38.3%) of them were intermediate education, while the majority 88.3% of them were housewives. As regard, age of studied children, the current study revealed that, more than half of the studied children were aged 12< 14 years, with Mean ±SD = 13.033±.839.…”
Section: Third Step: (Process Evaluation)mentioning
confidence: 99%
“…Meanwhile, this finding incomparable with Tęcza, & Pych . (2018) (27) : who studied" nursing care of a patient with systemic lupus erythematosus " and found that, more than half (55.9%) of the studied mothers were in the age group ≥ 40 years with ± SD was 39.62 ± 5.86 years and more than one third( 38.3%) of them were intermediate education, while the majority 88.3% of them were housewives. As regard, age of studied children, the current study revealed that, more than half of the studied children were aged 12< 14 years, with Mean ±SD = 13.033±.839.…”
Section: Third Step: (Process Evaluation)mentioning
confidence: 99%